East London: its foundation and early development as a port - Gordon, B C (Rhodes University, Faculty of Humanities, Department of History, 1932)
The flourishing city of East London has received but scant attention from historians. Its importance has been overshadowed by that of Cape Town, Durban and Port Elizabeth, each with a foundation bordering on the romantic. The introduction to this thesis indicates traces of the existence of primitive man in these parts. The historical survey will commence with notices taken of the region by nautical and land expeditions in search of either shipwrecked sailors, or news of native races. The first serious notice of East London taken by the white people came in the time of Sir Benjamin D'Urban who sought a seaport for his new province of Queen Adelaide. Our port was opened in 1836 under the appellation of Port Rex, but faded into temporary insignificance, almost oblivion, with the reversal of Sir. B. D'Urban's frontier policy by Lord Glenelg and the abandonment of the new province in 1837. It was not destined to remain forgotten, for Sir Harry Smith at the end of 1847, saw in the mouth of the Buffalo River the same possibilities as had struck the advisers of Sir B. D'Urban. To him it was the future London of the East, and the connecting link between British Kaffraria and the world outside. From that time East London has grown steadily, and of recent years very rapidly. It is not proposed to carry this survey much beyond 1866 in which year British Kaffraria was annexed to the Cape Colony.
Keywords: Smith, Harry George Wakelyn, Sir, 1788-1860; D'Urban, Benjamin, Sir, 1777-1849; Harbors -- South Africa -- East London; East London (South Africa) -- History -- 1836-1866